The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/dmcn.13194
|View full text |Cite
|
Sign up to set email alerts
|

Motorized versus manual instrumented spasticity assessment in children with cerebral palsy

Abstract: The differences in acceleration possibly account for the different muscle responses, which may suggest acceleration, rather than velocity-dependency of the stretch reflex. Future prototypes of instrumented spasticity assessments should standardize movement profiles, preferably by developing profiles that mimic functional tasks such as walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Instrumented spasticity assessment was carried out using a motor‐driven footplate (MOOG, Nieuw‐Vennep, The Netherlands) . The patient was seated in an adjustable chair with the right foot fixed onto a custom designed adjustable footplate (Figure C).…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrumented spasticity assessment was carried out using a motor‐driven footplate (MOOG, Nieuw‐Vennep, The Netherlands) . The patient was seated in an adjustable chair with the right foot fixed onto a custom designed adjustable footplate (Figure C).…”
Section: Investigationsmentioning
confidence: 99%
“…Instrumented spasticity assessment was carried out using a motor-driven footplate (MOOG, Nieuw-Vennep, The Netherlands). 11,18 The patient was seated in an adjustable chair with the right foot fixed onto a custom designed adjustable footplate 15,19 ( Figure 1C). This footplate allowed adjustments targeted to fix the talocalcaneal joint during foot plate rotations (for details see Huijing et al 15 ) The motor-driven footplate applied two slow (15°/s) and two fast (150°/s) speed controlled dorsiflexion movements over the patient's maximum ankle ROM (determined manually).…”
Section: Instrumented Spasticity Assessmentmentioning
confidence: 99%
“…This type of musculoskeletal modeling combined with spasticity measurement may allow for individually tailored spasticity treatments. Further, investigation of fast and slow passive rotations imposed during manual and motorized assessments may yield greater insights into the development of movement profiles to better mimic spasticity imposed during functional tasks such as walking (Sloot et al, 2016). …”
Section: Neuromuscular Deficits Of Cerebral Palsymentioning
confidence: 99%
“…Sloot 18 reported a battery of manual instrumentation-based tests, including measurements of joint velocity, imposed force, and muscle activity, used to objectively measure spasticity in CP. 18 The authors of that study verified that the measurements matched the subjects' gait profiles. Furthermore, Russian investigators have reported the use of an ultrasonographic technique to objectively evaluate the degree of muscle degeneration related to spasticity.…”
Section: Which Was Developed Bymentioning
confidence: 62%
“…It is also invasive and may be resisted by some children. Sloot reported a battery of manual instrumentation‐based tests, including measurements of joint velocity, imposed force, and muscle activity, used to objectively measure spasticity in CP . The authors of that study verified that the measurements matched the subjects’ gait profiles.…”
Section: Behavioral Assessments Of Pmdsmentioning
confidence: 86%